2021
DOI: 10.1055/a-1481-8905
|View full text |Cite|
|
Sign up to set email alerts
|

Meropenem Use in Pediatric Oncology – Audit on Indication, Appropriateness and Consumption Comparing Patient Derived and Pharmacy Dispensing Data

Abstract: Background Meropenem is an important second- or third-line antibiotic in pediatric cancer patients with febrile neutropenia (FN). Concise utilization data of meropenem in this setting is limited. It remains unclear how drug dispensing data from the hospital pharmacy correlate with data derived from patients’ files. Methods Retrospective audit of meropenem-consumption in a University-affiliated pediatric oncology center in days of therapy (DOT)/100 inpatient days. The individual indication for meropenem was cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Among the most frequent reasons for inappropriate therapy, incorrect dosing ranked first, followed by premature escalation during empiric treatment, lack of de-escalation, 13 and unnecessary use of antibiotic combinations for empirical therapy. 14 In accordance with other single center studies, 15 , 16 we found a high proportion of empirical carbapenem use (approximately 19%), 12 although a substantial proportion of carbapenem treatments were deemed inappropriate by expert panel adjudication. The higher prevalence of severe infections in pediatric oncology and hematology may explain this finding, as may carbapenem use in escalation therapy and/or high local resistance patterns (data not collected).…”
Section: Discussionsupporting
confidence: 89%
“…Among the most frequent reasons for inappropriate therapy, incorrect dosing ranked first, followed by premature escalation during empiric treatment, lack of de-escalation, 13 and unnecessary use of antibiotic combinations for empirical therapy. 14 In accordance with other single center studies, 15 , 16 we found a high proportion of empirical carbapenem use (approximately 19%), 12 although a substantial proportion of carbapenem treatments were deemed inappropriate by expert panel adjudication. The higher prevalence of severe infections in pediatric oncology and hematology may explain this finding, as may carbapenem use in escalation therapy and/or high local resistance patterns (data not collected).…”
Section: Discussionsupporting
confidence: 89%
“…Unfortunately, major issues exist in the methods used for measuring and reporting AC in children. These include the standard use of the inappropriate DDD metric, 4 , 5 estimations from dispensary data rather than actual patient-level administrations 6 and lack of paediatric-specific reporting. 7 , 8 This is a major barrier to benchmarking AC and sharing best antimicrobial stewardship (AMS) practices between centres and regions.…”
Section: Introductionmentioning
confidence: 99%